Suggested Strategic Effectiveness According To the NAGC Standards in Mathematics Achievement among Fifth-Grade Students Raghad Abdullah Kadhim (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the impact of teaching according to the effectiveness of a proposed strategy in light of the NAGC standards in mathematics achievement among fifth grade primary students. In order to verify the goal of the research, the researcher developed a null hypothesis stating the most effective strategic statement proposed in light of the NAGC criteria in mathematics achievement among fifth-grade students. As the current research was limited to fifth-grade primary school students in Al-Ibtikar Primary School of the Baghdad Education Directorate / Rusafa II, the second semester of the academic year (2018-2019) and to the seventh, eighth and ninth semesters of the mathematics textbook, the researcher chose two sections, by a simple random drawing method to represent the two experimental groups And control subjects. The number of the sample is (55) female students, (26) female students for the experimental group and (29) female students for the control group. The two groups of research were rewarded with variables (IQ test scores, previous achievement, chronological age calculated in months. The researcher formulated a test of "achievement" consisting of (30) questions for the three levels of bloom levels (knowledge, comprehension, application). The researcher also applied the achievement test in its final form consisting of (25) questions, and its validity and consistency were verified and the coefficient was calculated Difficulty, discriminatory strength, and effectiveness of false alternatives The results indicated that there was a statistically significant difference at the level of (05.0) between the mean scores of the experimental and control group pupils in favor of the experimental group in the achievement test. According to the results of the research, the researcher recommended the necessity of introducing mathematics teachers to modern teaching models, especially the effectiveness of some strategy in light of the NAGC standards in mathematics achievement, by holding training courses for this purpose, and including the curricula for preparing students of the Faculties of Education and Basic Education and teacher training institutes. The researcher also suggested conducting a study to compare teaching using a proposed strategy in light of the NAGC standards with other teaching methods, for different stages, other study materials, and other dependent variables (attitude, thinking of all kinds, multiple intelligences.